ANALISIS KOSAKATA YANG MENUNJUKAN PROFESI DALAM BUKU AJAR BAHASA JEPANG YANG DIGUNAKAN DI UNNES - Wibowo, Dida Aristo; Supriatnaningsih, Rina (Chi'e: Journal of Japanese Learning and Teaching, 2019)
Abstract (ANALYSIS OF VOCABULARY THAT SHOWS A PROFESSION FROM JAPANESE LANGUAGE BOOKS THAT USED IN UNNES) The important things in sentences is vocabulary. Vocabulary in Japanese is called 語彙‘goi’.Goi means a collection or set of words related to Japanese. Based on its origin, goi is divided into three types, 1) 和語 'Wago', are words in original Japanese, 2) 漢語 'Kango', are words that comes from China, and 3) 外来語 'Gairaigo', is an absorption word that comes from a foreign language, or most of it is from English. In learning vocabulary in Japanese, one of the groups of vocabulary that is often used is professional vocabulary. However, in the textbooks the types of professions have not been classified and how the form of professional vocabulary that as well as their used. The data source of this research is the Japanese textbook that used in the Japanese Language Education Study Program Unnes. The data analysis technique used in this research is the agih method and the technique of dividing elements directly. Based on the results of the research, the author obtained the professional words in Japanese language textbooks used in Unnes as many as 29 professional words, the word is classified in 23 words of Kango and 6 words of Gairaigo. The total occurrence in the textbook is 68 times. The word 会社員 (kaishain) occurs most often, which is 11 times.The author gets the word profession classified as Kango, which in its form is characterized by the suffix, which is ~者 (sha), ~員(in), ~士(shi), ~家(ka), ~手(syu), ~人(nin), ~事(ji). The author also gets the word profession belonging to Gairaigo based on the data which in its form is characterized by written using Katakana and a change in consonants or addition of vocals.   Abstrak Salah satu unsur penting dalam kalimat adalah kosakata. Kosakata dalam bahasa Jepang disebut 語彙‘goi’. Goi memiliki arti kumpulan atau himpunan kata yang berhubungan dengan bahasa Jepang. Berdasarkan asal usulnya, goi dibagi menjadi tiga macam yaitu, 1) 和語‘Wago’, merupakan kata-kata dalam bahasa Jepang asli, 2) 漢語‘Kango’, merupakan kata-kata yang dibaca secara onyomi dalam penulisan kanji, dan 3) 外来語‘Gairaigo’, merupakan kata-kata serapan yang berasal dari bahasa Asing, atau kebanyakan terdapat dari bahasa Inggris. Sumber data penelitian ini yaitu buku ajar bahasa Jepang yang digunakan di Prodi Pendidikan Bahasa Jepang Unnes.Teknik analisis data yang digunakan dalam penelitian ini adalah metode agih dan teknik bagi unsur langsung. Berdasarkan hasil penelitian, Penulis mendapatkan kata profesi dalam buku ajar bahasa Jepang yang digunakan di Unnes sebanyak 29 kata profesi, kata tersebut tergolong dalam 23 kata Kango dan 6 kata Gairaigo. Total kemunculan dalam buku ajar tersebut sebanyak 68 kali. Kata 会社員 (kaishain) paling sering muncul yaitu 11 kali. Penulis mendapatkan kata profesi yang tergolong Kango yang dalam pembentukannya ditandai dengan adanya sufiks yaitu ~者(sha), ~員(in), ~士(shi), ~家(ka), ~手(syu), ~人(nin), ~事(ji). Penulis juga mendapatkan kata profesi yang tergolong dalam Gairaigo yang berdasarkan data tersebut dapat ditandai pula secara penulisan ditulis dengan menggunakan Katakana dan adanya perubahan konsonan atau penambahan vokal. © 2019Universitas Negeri Semarang